The effects of hydrogen sulfide synthesis inhibition in lindane-induced seizures in rats: a behavioral and EEG study - Šutulović, Nikola; Rašić-Marković, Aleksandra; Grubač, Željko; Đurić, Emilija; Hrnčić, Dragan (Archives of Biological Sciences, 2020)
Paper description: Lindane-induced seizures in rats present a model of refractory generalized epilepsy. Hydrogen sulfide (H2S) is a gasotransmitter with different physiological roles. We examined the influence of aminooxyacetate, an inhibitor of H2S production, when applied before lindane administration. Convulsive behavior was assessed by seizure incidence, latency and severity. The number and duration of ictal periods in EEG were analyzed. Aminooxyacetate significantly decreased the latency and augmented the severity of seizures; EEG analysis revealed an increased number and duration of ictal periods. H2S production inhibition aggravated lindane-induced seizures, revealing a functional relationship between H2S and the effects of lindane. Abstract: Lindane-induced seizure in rats is a model of refractory generalized epilepsy. Hydrogen sulfide (H2S) is a gasotransmitter with different physiological and pathological roles. Cystathionine-β-synthase (CBS) is a major enzyme responsible for H2S production in the brain. The aim of this study was to investigate the effects of H2S production inhibition using aminooxyacetate (a CBS inhibitor) on behavioral and EEG manifestations of lindane-induced seizures. Male Wistar rats with previously implanted EEG electrodes were intraperitoneally (i.p.) treated with 4 mg/kg lindane and observed for convulsive behavior and EEG manifestations during the next 30 min. Aminooxyacetate (5, 15 and 25 mg/kg, i.p.) or saline, was injected 30 min prior to lindane. Convulsive behavior was assessed by seizure incidence, latency time and severity (grades 0-4). The number and duration of ictal periods in the EEG were also analyzed. Seizure incidence was higher in rats treated with aminooxyacetate (AOA) before lindane, but not significantly when compared with those treated only with lindane. However, AOA significantly decreased the latency time and augmented the severity of lindane-induced seizures in a dose-dependent manner. EEG analysis revealed an increased number and duration of ictal periods in rats receiving AOA prior to lindane. H2S production inhibition aggravated lindane-induced seizures, which showed a functional relationship between H2S and the effects of lindane.